Fire Extinguisher Wheel Robot Based on Arduino Mega 2560 R3 with Android Smartphone Control - Nugroho, Herry Setyo; Sutikno, Tole (Buletin Ilmiah Sarjana Teknik Elektro, 2021)
The development of technology in the smartphone sector is currently developing very rapidly which results in smartphones becoming one of the primary needs. Judging from the ability of a smartphone that is able to run various applications, one of which is to use it as a control tool. Through this research, a fire extinguisher wheeled robot prototype will be built with the control of an Android smartphone based on the Arduino Mega 2560 via Bluetooth wireless communication. The results showed that the robot can function properly controlled via an Android smartphone with a maximum distance of 10 meters, the robot is able to respond and extinguish the fire with a maximum range of 60 cm, and the robot is able to know the distance of the barrier around it (in cm) with an accuracy of up to 97%. To extinguish the fire the robot can move with an average speed of movement of the robot of 22.2 seconds per extinguishing phase.